2021
DOI: 10.1039/d1cp01041g
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the full relaxation dynamics of superexcited helium nanodroplets

Abstract: The relaxation dynamics of superexcited superfluid He nanodroplets is fully unravelled by means of extreme-ultraviolet (XUV) femtosecond electron and ion spectroscopy complemented by time-dependent density functional theory (TDDFT). Three main...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 72 publications
7
32
0
Order By: Relevance
“…From our investigation of the relaxation dynamics, it was found that the complete relaxation to the two lowest metastable states happens on a similar time-scale as ICD, but that the electronic (interband) relaxation is faster, and thus happens before the He superfluid dynamics sets in. 32 ICD of dopants appears to be driven by a similar medium-dominated dynamics as the He*+He* ICD process in pure droplets.…”
Section: Decay (Icd) Takes Places Either Between Two Excited He Atoms...mentioning
confidence: 91%
See 4 more Smart Citations
“…From our investigation of the relaxation dynamics, it was found that the complete relaxation to the two lowest metastable states happens on a similar time-scale as ICD, but that the electronic (interband) relaxation is faster, and thus happens before the He superfluid dynamics sets in. 32 ICD of dopants appears to be driven by a similar medium-dominated dynamics as the He*+He* ICD process in pure droplets.…”
Section: Decay (Icd) Takes Places Either Between Two Excited He Atoms...mentioning
confidence: 91%
“…For a discussion of the relaxation dynamics of superexcited pure He nanodroplets, we refer to our recent paper. 32 We start by presenting the results of static measurements (XUV only) for various doping levels of Na. Figure 1 shows photoelectron spectra (PES) of pure and Na-doped He nanodroplets of average size 4.1×10 4 atoms per droplet and a FEL intensity of 1.7×10 10 Wcm −2 .…”
Section: Decay (Icd) Takes Places Either Between Two Excited He Atoms...mentioning
confidence: 99%
See 3 more Smart Citations